Can conditional cash transfers impact institutional deliveries? Evidence from Janani Suraksha Yojana in India - Ambrish Dongrea (University of California, Economics Department, 2012)
Conditional cash transfers (CCTs) are an increasingly popular tool for incentivizing behavior. This paper evaluates impact of one of the largest CCTs in the world, Janani Suraksha Yojana (JSY) in India, on institutional deliveries. Maternal mortality is high in India and JSY aims to reduce it by encouraging institutional deliveries through provision of monetary incentives to women if they deliver in medical facilities, and to local community health workers if they facilitate such deliveries. Exploiting key differences in program design between the 'low performing' and the 'high performing' States, and utilizing successive rounds of a large national sample survey, this paper shows that institutional deliveries increased rapidly in the low performing States after the launch of the program, albeit with a lag. Pre-existing trends in institutional deliveries or improvement in availability or access to medical facilities do not explain these results.
Keywords: I18; O15; 330; Janani Suraksha Yojana; maternal mortality; institutional delivery; conditional cash transfer; India; National Rural Health Mission (NRHM)